Adult attachment styles and alcohol consumption in young adults - Cevallos-Robayo, Francis (2021)
The objective of this study was to describe the styles of adult attachment and alcohol consumption in young adults, measured through the CaMir-R test and the AUDIT questionnaire, analyzed under the InfoStat statistical program, respectively. Based on a sample of 167 young adults, men and women, between the ages of 18 and 32. The results show that 82.6% of the population is a consumer of alcohol with the highest prevalence in the secure attachment style, followed by the preoccupied insecure, insecure avoidant attachment style and the disorganized attachment indicator. The higher the level of alcohol consumption, the secure attachment scores decrease and rise in preoccupied insecure attachment style. The result does not statistically infer the linear causality of the study variables. The secure attachment style can function as a protective factor and the preoccupied insecure attachment as a risk factor for increasing the level of alcohol consumption.